LCP-based copper-clad plate as well as preparation method and application thereof
By using PTFE fiber cloth and multi-layer LCP film and metal film laminated structure in LCP-based copper clad plate, combined with hot pressing and vacuum copper plating technology, the problem of insufficient dielectric performance and bonding performance in the existing technology is solved, and the problem of insufficient dielectric performance and bonding performance is achieved. Excellent performance and high peel strength in high frequency communication.
Patent Information
- Application Number
- CN202411383131.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
It is difficult for existing LCP-based copper clad plates to have excellent dielectric properties and good copper layer bonding properties in high-frequency communication, resulting in weak dielectric properties or low peel strength.
The PTFE fiber cloth, multi-layer LCP film and metal film laminated structure is adopted, and the dielectric constant and dielectric loss are reduced by thermal pressing and vacuum copper plating, while the bonding force between the copper layer and the LCP film is enhanced.
It has achieved the improvement of dielectric performance and peel strength of LCP-based copper clad plate, and has excellent dielectric performance and good copper layer bonding performance. It is suitable for high-frequency and high-speed fields.
Smart Images

Figure CN119261326A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper clad laminates and relates to an LCP-based copper clad laminate, and in particular to an LCP-based copper clad laminate and a preparation method and application thereof. Background Art
[0002] At present, with the development of high-frequency communication, the quality requirements for copper clad laminates are getting higher and higher, and liquid crystal epoxy polymer (LCP) has very excellent dielectric properties and is widely used in high-frequency and high-speed copper clad laminates. The conventional method of LCP-based copper clad laminates is to press the LCP film with the copper foil. The adhesion between the copper foil and LCP obtained by this process is poor, which is easy to cause shedding or bubbling during the PCB processing process, thus affecting the application of high-frequency PCBs.
[0003] CN102922809A discloses a liquid crystal polymer peeling fiber adhesive sheet, a copper clad laminate and a preparation method thereof, wherein a composite layer consisting of a laminated structure of "LCP layer / glass fiber cloth / LCP layer" is used as a bonding unit, and a laminated blank is assembled in the stacking order of "copper foil / bonding unit / copper foil", and then a laminator is used to pressurize and heat to form a liquid crystal polymer glass fiber cloth-based copper clad laminate, wherein the mechanical properties are improved, but the dielectric properties of the material are sacrificed, and the peel strength of the copper clad laminate is still low.
[0004] CN208175088U discloses a high-frequency and high-speed substrate, including an LCP substrate, an adhesive layer and a PI layer, wherein the LCP substrate includes a copper foil, an LCP dielectric layer and a copper wire, wherein the LCP dielectric layer is located on the copper foil, and the copper wire is distributed on the dielectric layer; the adhesive layer covers the LCP dielectric layer on which the copper wire is distributed, and the PI layer is connected to the LCP substrate through the adhesive layer. Due to the excellent dielectric properties of the LCP material, the attenuation of the entire substrate during high-frequency and high-speed signal transmission is reduced, and the circuit can be protected by using a PI layer on one side of the copper wire. This high-frequency and high-speed substrate takes advantage of the low dielectric constant and dielectric loss of LCP, and effectively improves the dielectric properties of the substrate, but its dielectric properties are weaker than those of pure LCP, and the peel strength of the copper-clad laminate is relatively low.
[0005] CN117255501A discloses a method for making a copper-clad laminate with metallized holes, comprising the following steps: drilling holes in an insulating substrate; pre-treating the substrate with holes; treating the surface of the substrate and the hole wall simultaneously in a combination of multiple physical vapor deposition methods to form a conductive seed layer on the surface of the substrate and the hole wall, thereby obtaining a metallized substrate with metallized holes; and electroplating and thickening the metallized substrate to obtain a copper-clad laminate with metallized holes. However, the dielectric properties of the copper-clad laminate obtained by this method are low and cannot meet the needs of practical applications.
[0006] The LCP-based copper-clad laminate and its preparation method disclosed in the prior art have certain defects, and there is a problem that it is impossible to have both excellent dielectric properties and good copper layer bonding performance. Therefore, it is very important to develop and design a new type of LCP-based copper-clad laminate and its preparation method. Summary of the invention
[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide an LCP-based copper-clad laminate and a preparation method and application thereof. In the LCP-based copper-clad laminate provided by the present invention, a PTFE fiber cloth with a low dielectric constant and dielectric loss is stacked with a first LCP film and a second LCP film, thereby reducing the dielectric constant and dielectric loss of the LCP-based copper-clad laminate finally obtained; in addition, in the LCP-based copper-clad laminate provided by the present invention, a first metal film is arranged between the first LCP film and the first copper layer, and a second metal film is arranged between the second LCP film and the second copper layer, thereby enhancing the bonding force between the first LCP film and the first copper layer, and the bonding force between the second LCP film and the second copper layer, thereby improving the peel strength of the LCP-based copper-clad laminate. Therefore, the LCP-based copper-clad laminate provided by the present invention has both excellent dielectric properties and good copper layer bonding properties.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides an LCP-based copper-clad laminate, comprising a PTFE fiber cloth; and on a surface of one side of the PTFE fiber cloth, a first LCP film, a first metal film and a first copper layer are stacked in sequence along a direction away from the PTFE fiber cloth; and on the surface of the other side of the PTFE fiber cloth, a second LCP film, a second metal film and a second copper layer are stacked in sequence along a direction away from the PTFE fiber cloth.
[0010] In the present invention, the first LCP film and the second LCP film can be original LCP films or modified LCP films, which will not affect the realization of the effects of the present invention. For example, the use of modified LCP films with improved dielectric properties or adhesion properties is also suitable for this application, and is used to further improve the dielectric properties and bonding properties of the LCP-based copper clad laminate.
[0011] In the LCP-based copper-clad laminate provided by the present invention, a PTFE fiber cloth with low dielectric constant and dielectric loss is stacked with a first LCP film and a second LCP film, thereby reducing the dielectric constant and dielectric loss of the LCP-based copper-clad laminate finally obtained; in addition, in the LCP-based copper-clad laminate provided by the present invention, a first metal film is arranged between the first LCP film and the first copper layer, and a second metal film is arranged between the second LCP film and the second copper layer, thereby enhancing the bonding force between the first LCP film and the first copper layer, and the bonding force between the second LCP film and the second copper layer, thereby improving the peel strength of the LCP-based copper-clad laminate. Therefore, the LCP-based copper-clad laminate provided by the present invention has both excellent dielectric properties and good copper layer bonding properties.
[0012] Preferably, the thickness of the PTFE fiber cloth is 10 to 200 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, the thickness of the first LCP film and the second LCP film are independently 20 to 100 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the thickness of the first metal film and the second metal film are independently 100 to 400 nm, for example, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, 300 nm, 320 nm, 350 nm, 380 nm or 400 nm, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, the thickness of the first copper layer and the second copper layer are independently 3 to 35 μm, for example, 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 25 μm, 30 μm, 32 μm or 35 μm, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] Preferably, the first metal film and the second metal film independently include any one of copper film, nickel film or gold film, or a combination of at least two of them. Typical but non-limiting combinations include a combination of copper film and nickel film, a combination of nickel film and gold film, or a combination of copper film, nickel film and gold film.
[0017] In a second aspect, the present invention provides a method for preparing the LCP-based copper-clad laminate according to the first aspect, the preparation method comprising:
[0018] A first LCP film, a PTFE fiber cloth and a second LCP film stacked in sequence are heat pressed to obtain a high-frequency and high-speed LCP adhesive film; a first metal film and a second metal film are first deposited on both side surfaces of the obtained high-frequency and high-speed LCP adhesive film, and a first copper layer and a second copper layer are second deposited on the surfaces of the obtained first metal film and the second metal film to obtain an LCP-based copper-clad laminate.
[0019] In the preparation method provided by the present invention, a PTFE fiber cloth with a low dielectric constant is heat-pressed with a first LCP film and a second LCP film to obtain a high-frequency and high-speed LCP adhesive film with a low dielectric constant, thereby reducing the dielectric constant of the LCP-based copper-clad laminate finally obtained; in addition, in the preparation method, the high-frequency and high-speed LCP adhesive film is vacuum-plated with a metal film and then plated with a copper layer, thereby improving the bonding strength between the high-frequency and high-speed LCP adhesive film and the copper layer, thereby improving the peel strength of the prepared LCP-based copper-clad laminate; thirdly, the preparation method has simple steps and is environmentally friendly.
[0020] Preferably, the temperature of the hot pressing is 270-320° C., the pressure is 3-10 MPa, and the pressing time is 50-120 min.
[0021] The temperature of the hot pressing in the present invention is 270-320°C, for example, it can be 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C or 320°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] The heat pressing pressure in the present invention is 3 to 10 MPa, for example, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The hot pressing time of the present invention is 50 to 120 minutes, for example, it can be 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the first deposition method includes physical vapor deposition.
[0025] Preferably, the power of the physical vapor deposition is 5-60 kW, the temperature is 200-400°C, and the absolute vacuum is ≤1×10 -3 Pa.
[0026] The power of physical vapor deposition described in the present invention is 5 to 60 kW, for example, it can be 5kW, 10kW, 15kW, 20kW, 25kW, 30kW, 35kW, 40kW, 45kW, 50kW, 55kW or 60kW, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] The temperature of the physical vapor deposition described in the present invention is 200-400°C, for example, it can be 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] The absolute vacuum degree of the physical vapor deposition in the present invention is ≤1×10 -3 Pa, for example, can be 1×10 -3 Pa, 0.9×10 -3 Pa, 0.8×10 -3 Pa, 0.7×10 -3 Pa, 0.6×10 -3 Pa, 0.4×10 -3 Pa, 0.2×10 -3 Pa or 0.1×10 - 3 Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the first deposition method includes chemical plating and / or electroplating.
[0030] The relevant parameters of electroplating in the present invention are selected according to the conventional requirements in the field to ensure that the first copper layer and the second copper layer of the thickness in the present application can be obtained.
[0031] The plating solution used in the chemical plating and electroplating of the present invention is selected according to the conventional requirements in the art to ensure that the first copper layer and the second copper layer of the thickness in the present application can be obtained; the composition of the plating solution used for electroplating in the present invention can be, for example: 120g / L anhydrous copper sulfate, 190g / L sulfuric acid, 65ppm Cl - , 14 mL / L of AM-108 (purchased from Kunshan Hongqi Trading Co., Ltd.) and 0.5 mL / L of AM-108B (purchased from Kunshan Hongqi Trading Co., Ltd.).
[0032] Preferably, the pH of the plating solution during electroplating is 1 to 3, and the current density is 1.9 to 2.3 A / dm 2 , the temperature is 20-25℃.
[0033] The pH of the plating solution during electroplating in the present invention is 1 to 3, for example, it can be 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8 or 3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] The current density during electroplating in the present invention is 1.9 to 2.3 A / dm 2 , for example, it can be 1.9A / dm 2 , 1.95A / dm 2 , 2A / dm 2 , 2.05A / dm 2 , 2.1A / dm 2 , 2.15A / dm 2 , 2.2A / dm 2 , 2.25A / dm 2 or 2.3A / dm 2 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] The temperature during electroplating in the present invention is 20-25°C, for example, it can be 20°C, 20.5°C, 21°C, 21.5°C, 22°C, 22.5°C, 23°C, 23.5°C, 24°C, 24.5°C or 25°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the preparation method further comprises performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film respectively before the thermal pressing.
[0037] In the present invention, after the first plasma treatment is performed on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film, the bonds on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film can be broken and the CO bonds and -OH bonds can be joined, which can effectively enhance the surface activity of the first LCP film, the PTFE fiber cloth and the second LCP film, and then hot pressing is performed to effectively improve the bonding strength between the first LCP film, the PTFE fiber cloth and the second LCP film.
[0038] Before the first plasma treatment in the present invention, surface cleaning can be optionally performed to remove residual agents, stains and other impurities that affect the product on the surfaces of the first LCP film, PTFE fiber cloth and second LCP film. Specifically, water washing and / or alcohol washing can be selected.
[0039] Preferably, the preparation method further comprises performing a second plasma treatment on both side surfaces of the obtained high-frequency and high-speed LCP film before the first deposition.
[0040] In the present invention, by performing a second plasma treatment on the surfaces of the first LCP film and the second LCP film of the high-frequency and high-speed LCP film, and then performing a second deposition, the metal molecules of the first metal film and the second metal film can be combined with the surface of the LCP film after the plasma treatment by forming a chemical bond (OX, X is any one of nickel, copper or gold or a combination of at least two), and then the first copper layer and the second copper layer are deposited, thereby greatly enhancing the bonding strength between the high-frequency and high-speed LCP film and the first copper layer and the second copper layer.
[0041] Preferably, the gases used in the first plasma treatment and the second plasma treatment independently include any one of H2, NH3, Ar, O2 or CF4, or a combination of at least two of them. Typical but non-limiting combinations include a combination of H2 and NH3, a combination of Ar and O2, a combination of O2 and CF4, a combination of H2, NH3 and Ar, or a combination of H2, CF4 and O2.
[0042] Preferably, the gases used in the first plasma treatment and the second plasma treatment independently include H2, CF4 and O2 in a volume ratio of (1 to 2.5):1:1. The volume ratio can be, for example, 1:1:1, 1.2:1:1, 1.4:1:1, 1.6:1:1, 1.8:1:1, 2:1:1, 2.1:1:1, 2.3:1:1 or 2.5:1:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0043] In the present invention, when the gases used in the first plasma treatment and the second plasma treatment are H2, CF4 and O2 in a volume ratio of (1 to 2.5):1:1, the surface treatment effect of the plasma can be significantly improved, the bonding effect can be significantly improved, and at the same time, the obtained LCP-based copper clad laminate can be further ensured to have good dielectric properties.
[0044] Preferably, the flow rates of the gases used in the first plasma treatment and the second plasma treatment are independently 30 to 80 mL / min, for example, 30 mL / min, 35 mL / min, 40 mL / min, 45 mL / min, 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, 75 mL / min or 80 mL / min, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the power used in the first plasma treatment and the second plasma treatment is independently 200-2000 W, for example, 200 W, 400 W, 600 W, 800 W, 1000 W, 1200 W, 1400 W, 1600 W, 1800 W or 2000 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the absolute vacuum degree in the first plasma treatment and the second plasma treatment is independently ≤1×10 -6 Pa, for example, can be 1×10 -6 Pa, 0.9×10 -6 Pa, 0.8×10 -6 Pa, 0.7×10 -6 Pa, 0.6×10 -6 Pa, 0.5×10 -6 Pa, 0.4×10 -6 Pa, 0.3×10 -6 Pa, 0.2×10 -6 Pa or 0.1×10 -6 Pa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the temperatures in the first plasma treatment and the second plasma treatment are independently 80-300°C, for example, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C or 300°C, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the time for the first plasma treatment and the second plasma treatment is independently 5 to 60 minutes, for example, it can be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:
[0050] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film respectively, and performing heat pressing for 50 to 120 minutes at a temperature of 270 to 320° C. and a pressure of 3 to 10 MPa on the first LCP film, the PTFE fiber cloth and the second LCP film, which are sequentially stacked and arranged after the first plasma treatment, to obtain a high-frequency and high-speed LCP adhesive film;
[0051] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 5 to 60 kW, a temperature of 200 to 400° C., and a temperature of ≤1×10 -3 Pa, performing physical vapor deposition of a first metal film and a second metal film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first metal film and the second metal film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate;
[0052] The gases used in the first plasma treatment and the second plasma treatment independently include H2, CF4 and O2 in a volume ratio of (1-2.5):1:1; the flow rate of the gases used in the first plasma treatment and the second plasma treatment is independently 30-80 mL / min, the power used is independently 200-2000 W, and the absolute vacuum degree is independently ≤1×10 -6 Pa, the temperature is independently 80 to 300° C., and the time is independently 5 to 60 min.
[0053] In a third aspect, the present invention provides an application of the LCP-based copper clad laminate described in the first aspect, wherein the LCP-based copper clad laminate is used as a raw material in the field of high frequency and high speed.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] (1) In the LCP-based copper-clad laminate provided by the present invention, a PTFE fiber cloth with a low dielectric constant and dielectric loss is stacked with a first LCP film and a second LCP film, thereby reducing the dielectric constant and dielectric loss of the final LCP-based copper-clad laminate; in addition, in the LCP-based copper-clad laminate provided by the present invention, a first metal film is arranged between the first LCP film and the first copper layer, and a second metal film is arranged between the second LCP film and the second copper layer, thereby enhancing the bonding force between the first LCP film and the first copper layer, and the bonding force between the second LCP film and the second copper layer, thereby improving the peel strength of the LCP-based copper-clad laminate. Therefore, the LCP-based copper-clad laminate provided by the present invention has both excellent dielectric properties and good copper layer bonding properties;
[0056] (2) In the preparation method provided by the present invention, the PTFE fiber cloth with a low dielectric constant is heat-pressed with the first LCP film and the second LCP film to obtain a high-frequency and high-speed LCP adhesive film with a low dielectric constant, thereby reducing the dielectric constant of the LCP-based copper-clad laminate finally obtained; in addition, in the preparation method, the high-frequency and high-speed LCP adhesive film is vacuum-plated with a metal film and then copper-plated, thereby improving the bonding force between the high-frequency and high-speed LCP adhesive film and the copper layer, thereby improving the peel strength of the prepared LCP-based copper-clad laminate; again, the preparation method has simple steps and is environmentally friendly;
[0057] (3) In the present invention, after the first plasma treatment is performed on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film, the bonds on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film can be broken and CO bonds and -OH bonds can be bonded, which can effectively enhance the surface activity of the first LCP film, the PTFE fiber cloth and the second LCP film, and then hot pressing is performed, thereby effectively improving the bonding strength between the first LCP film, the PTFE fiber cloth and the second LCP film;
[0058] (4) In the present invention, by performing a second plasma treatment on the surfaces of the first LCP film and the second LCP film of the high-frequency and high-speed LCP film, and then performing a second deposition, the metal molecules of the first metal film and the second metal film can form a chemical bond (OX, X is any one of nickel, copper or gold or a combination of at least two) with the surface of the LCP film after the plasma treatment, and then the first copper layer and the second copper layer are deposited, thereby greatly enhancing the bonding strength between the high-frequency and high-speed LCP film and the first copper layer and the second copper layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a schematic structural diagram of the LCP-based copper clad laminate provided in Example 1 of the present invention.
[0060] Among them, 1-PTFE fiber cloth; 2-first LCP film; 3-first copper film; 4-first copper layer; 5-second LCP film; 6-second copper film; 7-second copper layer. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a Figure 1 The LCP-based copper-clad laminate shown in the figure comprises a PTFE fiber cloth 1 with a thickness of 80 μm; and on one side surface of the PTFE fiber cloth 1, a first LCP film 2 with a thickness of 50 μm, a first copper film 3 with a thickness of 100 nm, and a first copper layer 4 with a thickness of 35 μm are sequentially stacked in a direction away from the PTFE fiber cloth 1; and on the other side surface of the PTFE fiber cloth 1, a second LCP film 5 with a thickness of 50 μm, a second copper film 6 with a thickness of 100 nm, and a second copper layer 7 with a thickness of 35 μm are sequentially stacked in a direction away from the PTFE fiber cloth 1.
[0064] The preparation method of the LCP-based copper-clad laminate comprises:
[0065] (1) performing a first plasma treatment on the surfaces of the first LCP film 2, the PTFE fiber cloth 1 and the second LCP film 5 respectively, and performing heat pressing for 90 minutes at a temperature of 280° C. and a pressure of 5 MPa on the first LCP film 2, the PTFE fiber cloth 1 and the second LCP film 5 which are sequentially stacked after the first plasma treatment, to obtain a high-frequency and high-speed LCP adhesive film;
[0066] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gases used in the first plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min;
[0067] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 10 kW, a temperature of 250° C., and a temperature of 1×10 -3Pa, after physical vapor deposition of a first copper film 3 and a second copper film 6, a first copper layer 4 and a second copper layer 7 are deposited independently on the surfaces of the first copper film 3 and the second copper film 6 by electroplating, to obtain an LCP-based copper-clad laminate;
[0068] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gases used in the second plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum is independently 0.5×10 -6 Pa, temperature is 120℃, time is 10min.
[0069] Example 2
[0070] The present embodiment provides an LCP-based copper-clad laminate, which includes a PTFE fiber cloth with a thickness of 80 μm; and on one side surface of the PTFE fiber cloth, a first LCP film with a thickness of 50 μm, a first nickel film with a thickness of 100 nm, and a first copper layer with a thickness of 35 μm are stacked in sequence in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film with a thickness of 50 μm, a second nickel film with a thickness of 100 nm, and a second copper layer with a thickness of 35 μm are stacked in sequence in a direction away from the PTFE fiber cloth.
[0071] The preparation method of the LCP-based copper-clad laminate comprises:
[0072] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth, and the second LCP film, respectively, and performing heat pressing on the first LCP film, the PTFE fiber cloth, and the second LCP film stacked in sequence at a temperature of 280° C. and a pressure of 8 MPa for 90 min to obtain a high-frequency and high-speed LCP adhesive film;
[0073] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gases used in the first plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min;
[0074] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 10 kW, a temperature of 250° C., and a temperature of 1×10 -3Pa, performing physical vapor deposition of a first nickel film and a second nickel film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first nickel film and the second nickel film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate;
[0075] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gas used in the second plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min.
[0076] Example 3
[0077] The present embodiment provides an LCP-based copper-clad laminate, which includes a PTFE fiber cloth with a thickness of 50 μm; and on one side surface of the PTFE fiber cloth, a first LCP film with a thickness of 50 μm, a first copper film with a thickness of 100 nm, and a first copper layer with a thickness of 35 μm are sequentially stacked in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film with a thickness of 50 μm, a second copper film with a thickness of 100 nm, and a second copper layer with a thickness of 35 μm are sequentially stacked in a direction away from the PTFE fiber cloth.
[0078] The preparation method of the LCP-based copper-clad laminate comprises:
[0079] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth, and the second LCP film, respectively, and performing heat pressing on the first LCP film, the PTFE fiber cloth, and the second LCP film stacked in sequence at a temperature of 290° C. and a pressure of 8 MPa for 90 min to obtain a high-frequency and high-speed LCP adhesive film;
[0080] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gases used in the first plasma treatment is 50 mL / min, the power used is 500 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min;
[0081] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 5 kW, a temperature of 200° C., and a temperature of 1×10 -3Pa, performing physical vapor deposition of a first copper film and a second copper film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first copper film and the second copper film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate;
[0082] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gas used in the second plasma treatment is 50 mL / min, the power used is 500 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min.
[0083] Example 4
[0084] The present embodiment provides an LCP-based copper-clad laminate, which includes a PTFE fiber cloth with a thickness of 50 μm; and on one side surface of the PTFE fiber cloth, a first LCP film with a thickness of 50 μm, a first copper film with a thickness of 400 nm, and a first copper layer with a thickness of 3 μm are sequentially stacked in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film with a thickness of 50 μm, a second copper film with a thickness of 400 nm, and a second copper layer with a thickness of 3 μm are sequentially stacked in a direction away from the PTFE fiber cloth.
[0085] The preparation method of the LCP-based copper-clad laminate comprises:
[0086] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth, and the second LCP film, respectively, and performing heat pressing on the first LCP film, the PTFE fiber cloth, and the second LCP film stacked in sequence at a temperature of 300° C. and a pressure of 5 MPa for 90 min to obtain a high-frequency and high-speed LCP adhesive film;
[0087] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gases used in the first plasma treatment is 50 mL / min, the power used is 800 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min;
[0088] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 60 kW, a temperature of 400° C., and a temperature of 1×10 -3Pa, performing physical vapor deposition of a first copper film and a second copper film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first copper film and the second copper film by electroplating to obtain an LCP-based copper-clad laminate;
[0089] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gas used in the second plasma treatment is 50 mL / min, the power used is 800 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min.
[0090] Example 5
[0091] The present embodiment provides an LCP-based copper-clad laminate, which includes a PTFE fiber cloth with a thickness of 10 μm; and on one side surface of the PTFE fiber cloth, a first LCP film with a thickness of 20 μm, a first copper film with a thickness of 150 nm, and a first copper layer with a thickness of 10 μm are sequentially stacked in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film with a thickness of 20 μm, a second copper film with a thickness of 150 nm, and a second copper layer with a thickness of 10 μm are sequentially stacked in a direction away from the PTFE fiber cloth.
[0092] The preparation method of the LCP-based copper-clad laminate comprises:
[0093] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth, and the second LCP film, respectively, and performing heat pressing on the first LCP film, the PTFE fiber cloth, and the second LCP film stacked in sequence at a temperature of 270° C. and a pressure of 10 MPa for 50 min to obtain a high-frequency and high-speed LCP adhesive film;
[0094] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 1:1:1; the flow rate of the gases used in the first plasma treatment is 30 mL / min, the power used is 200 W, and the absolute vacuum degree is 0.1×10 -6 Pa, temperature is 300℃, time is 5min;
[0095] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 60 kW, a temperature of 200° C., and a temperature of 0.1×10 -3Pa, performing physical vapor deposition of a first copper film and a second copper film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first copper film and the second copper film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate;
[0096] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 2.5:1:1; the flow rate of the gas used in the second plasma treatment is 80 mL / min, the power used is 2000 W, and the absolute vacuum degree is 1×10 -6 Pa, temperature is 80℃, time is 60min.
[0097] Example 6
[0098] The present embodiment provides an LCP-based copper-clad laminate, which includes a PTFE fiber cloth with a thickness of 200 μm; and on one side surface of the PTFE fiber cloth, a first LCP film with a thickness of 100 μm, a first metal film with a thickness of 400 nm, and a first copper layer with a thickness of 25 μm are sequentially stacked in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film with a thickness of 100 μm, a second metal film with a thickness of 400 nm, and a second copper layer with a thickness of 25 μm are sequentially stacked in a direction away from the PTFE fiber cloth.
[0099] The first metal film and the second metal film independently include any one of a copper film, a nickel film or a gold film, or a combination of at least two of them.
[0100] The preparation method of the LCP-based copper-clad laminate comprises:
[0101] (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth, and the second LCP film, respectively, and performing heat pressing for 120 min at a temperature of 320° C. and a pressure of 3 MPa on the first LCP film, the PTFE fiber cloth, and the second LCP film, which are sequentially stacked and arranged after the first plasma treatment, to obtain a high-frequency and high-speed LCP adhesive film;
[0102] The gases used in the first plasma treatment are H2, CF4 and O2 in a volume ratio of 2.5:1:1; the flow rate of the gases used in the first plasma treatment is 80 mL / min, the power used is 2000 W, and the absolute vacuum degree is 1×10 -6 Pa, temperature is 80℃, time is 60min;
[0103] (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 5 kW, a temperature of 400° C., and a temperature of 1×10 -3 Pa, performing physical vapor deposition of a first metal film and a second metal film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first metal film and the second metal film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate;
[0104] The gases used in the second plasma treatment are H2, CF4 and O2 in a volume ratio of 1:1:1; the flow rate of the gas used in the second plasma treatment is 30 mL / min, the power used is 200 W, and the absolute vacuum degree is 0.1×10 -6 Pa, temperature is 300℃, time is 5min.
[0105] Example 7
[0106] The present embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the gases used in the first plasma treatment in step (1) and the second plasma treatment in step (2) of the method for preparing the LCP-based copper-clad laminate are replaced with a mixed gas of CF4 and O2 in a volume ratio of 1:1.
[0107] Example 8
[0108] The present embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the gases used in the first plasma treatment in step (1) and the second plasma treatment in step (2) of the method for preparing the LCP-based copper-clad laminate are replaced with a mixed gas of H2 and O2 in a volume ratio of 1:1.
[0109] Example 9
[0110] The present embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the gases used in the first plasma treatment in step (1) and the second plasma treatment in step (2) of the method for preparing the LCP-based copper-clad laminate are replaced with a mixed gas of CF4, NH3 and O2 in a volume ratio of 2:1:1.
[0111] Example 10
[0112] The present embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the gases used in the first plasma treatment in step (1) and the second plasma treatment in step (2) of the preparation method of the LCP-based copper-clad laminate are replaced with O2.
[0113] Embodiment 11
[0114] This embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the first plasma treatment in step (1) of the method for preparing the LCP-based copper-clad laminate is omitted.
[0115] Example 12
[0116] This embodiment provides an LCP-based copper-clad laminate, which is the same as Embodiment 1 except that the second plasma treatment in step (2) of the method for preparing the LCP-based copper-clad laminate is omitted.
[0117] Embodiment 13
[0118] This embodiment provides an LCP-based copper-clad laminate, which is the same as that of Embodiment 1 except that the thickness of the PTFE fiber cloth is 5 μm.
[0119] Embodiment 14
[0120] This embodiment provides an LCP-based copper-clad laminate, which is the same as that of Embodiment 1 except that the thickness of the PTFE fiber cloth is 300 μm.
[0121] Comparative Example 1
[0122] The present comparative example provides an LCP-based copper clad laminate, which is the same as Example 1 except that step (2) of the preparation method of the LCP-based copper clad laminate is replaced, and the rest is the same as Example 1, and step (2) is replaced by: directly heating and pressing a stacked first copper foil with a thickness of 35 μm, the high-frequency and high-speed LCP film obtained in step (1), and a second copper foil with a thickness of 35 μm, wherein the heating and pressing pressure is 5 MPa, the pressing temperature is 280° C., and the pressing time is 90 min, to obtain an LCP-based copper clad laminate.
[0123] Comparative Example 2
[0124] The present comparative example provides an LCP-based copper clad laminate, which is the same as Example 1 except that step (2) of the preparation method of the LCP-based copper clad laminate is replaced, and the rest are the same as Example 1, and step (2) is replaced by: performing a second plasma treatment on both side surfaces of the high-frequency and high-speed LCP film obtained in step (1), and then directly heating and pressing the stacked first copper foil with a thickness of 35 μm, the high-frequency and high-speed LCP film after the second plasma treatment, and the second copper foil with a thickness of 35 μm, wherein the pressure of the heating and pressing is 5 MPa, the pressing temperature is 280° C., and the pressing time is 90 min, to obtain the LCP-based copper clad laminate; the gas used in the second plasma treatment is H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gas used in the second plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum degree is independently 0.5×10 -6Pa, temperature is 120℃, time is 10min.
[0125] Comparative Example 3
[0126] The present comparative example provides an LCP-based copper-clad laminate, which is the same as Example 1 except that step (1) of the preparation method of the LCP-based copper-clad laminate is replaced by: performing a first plasma treatment on the surfaces of the first LCP film and the second LCP film respectively, and performing heat pressing on the first LCP film and the second LCP film after the first plasma treatment at a temperature of 280° C. and a pressure of 5 MPa for 90 min to obtain a high-frequency and high-speed LCP adhesive film; the gas used in the first plasma treatment is H2, CF4 and O2 in a volume ratio of 2:1:1; the flow rate of the gas used in the first plasma treatment is 50 mL / min, the power used is 300 W, and the absolute vacuum degree is 0.5×10 -6 Pa, temperature is 120℃, time is 10min.
[0127] The LCP-based copper-clad laminates obtained in the above examples and comparative examples were tested for dielectric constant and dielectric loss according to IEC 61189-2-721 (2015-04) standard at a frequency of 10 GHz, and the test results are shown in Table 1; the peel strength of the LCP-based copper-clad laminates was tested according to IPC-TM-6502.4.8 standard, and the test results are shown in Table 1.
[0128] Table 1
[0129]
[0130]
[0131] From Table 1, we can get:
[0132] (1) The LCP-based copper-clad laminates provided in Examples 1 to 6 have a lower dielectric constant, smaller dielectric loss and higher peel strength. The LCP-based copper-clad laminates provided by the present invention also have excellent dielectric properties and good copper layer bonding properties;
[0133] (2) By comparing Example 1 with Examples 7 to 10, it can be seen that the gas environment used in the first plasma treatment and the second plasma treatment in the present invention will affect the performance of the LCP-based copper-clad laminate; in the present invention, when the gases used in the first plasma treatment and the second plasma treatment are H2, CF4 and O2 in a volume ratio of (1 to 2.5): 1: 1, the surface treatment effect of the plasma can be significantly improved, the bonding effect can be significantly improved, and at the same time, the obtained LCP-based copper-clad laminate can be further ensured to have good dielectric properties;
[0134] (3) By comparing Example 1 with Examples 11 and 12, it can be seen that in the present invention, after the first plasma treatment is performed on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film, the bonds on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film can be broken and CO bonds and -OH bonds can be bonded, which can effectively enhance the surface activity of the first LCP film, the PTFE fiber cloth and the second LCP film, and then hot pressing is performed to effectively improve the bonding strength between the first LCP film, the PTFE fiber cloth and the second LCP film; in the present invention, by performing a second plasma treatment on the surfaces of the first LCP film and the second LCP film of the high-frequency and high-speed LCP film, and then performing a second deposition, the metal molecules of the first metal film and the second metal film can be combined with the surface of the LCP film after the plasma treatment by forming a chemical bond (OX, X is any one of nickel, copper or gold or a combination of at least two), and then the first copper layer and the second copper layer are deposited, thereby greatly enhancing the bonding strength between the high-frequency and high-speed LCP film and the first copper layer and the second copper layer;
[0135] (4) By comparing Example 1 with Examples 13 and 14, it can be seen that the thickness of the PTFE fiber cloth in the present invention affects the performance of the LCP-based copper-clad laminate; when the thickness of the PTFE fiber cloth is 10 to 200 μm, it is more conducive to simultaneously improving the dielectric properties and bonding properties of the LCP-based copper-clad laminate. This is because if the PTFE is too thick, it will increase the difficulty of obtaining the raw materials and will also make it impossible for the LCP to completely infiltrate the PTFE fiber cloth; and if the PTFE is too thin, the effect on the overall dielectric properties of the film is small, and it cannot play a role in improving the dielectric properties of the film;
[0136] (5) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that in the present invention, the copper foil is directly pressed without plasma surface treatment, and there is no chemical bond between the adhesive film and the copper foil, and the bonding force is weak, so that the peel strength is very low; after the adhesive film is plasma treated, the first metal film and the second metal film are not deposited, and the copper foil is directly pressed, and the peel strength is still low;
[0137] (6) By comparing Example 1 with Comparative Example 3, it can be seen that when the PTFE fiber cloth is omitted in the present invention, the dielectric constant of the LCP-based copper-clad laminate is higher and the mechanical properties are weaker; in the LCP-based copper-clad laminate provided by the present invention, the PTFE fiber cloth with lower dielectric constant and dielectric loss is stacked with the first LCP film and the second LCP film, thereby reducing the dielectric constant and dielectric loss of the final LCP-based copper-clad laminate; in addition, when the PTFE fiber cloth is omitted, the LCP-based copper-clad laminate lacks the support effect of the PTFE fiber cloth, and the mechanical properties will also deteriorate.
[0138] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. An LCP-based copper-clad laminate, characterized in that: The LCP-based copper-clad laminate includes a PTFE fiber cloth; and on one side surface of the PTFE fiber cloth, a first LCP film, a first metal film and a first copper layer are stacked in sequence in a direction away from the PTFE fiber cloth; and on the other side surface of the PTFE fiber cloth, a second LCP film, a second metal film and a second copper layer are stacked in sequence in a direction away from the PTFE fiber cloth.
2. The LCP-based copper-clad laminate according to claim 1, characterized in that: The thickness of the PTFE fiber cloth is 10 to 200 μm; Preferably, the thickness of the first LCP film and the second LCP film are independently 20 to 100 μm; Preferably, the thickness of the first metal film and the second metal film are independently 100-400 nm; Preferably, the thickness of the first copper layer and the second copper layer are independently 3 to 35 μm; Preferably, the first metal film and the second metal film independently include any one of a copper film, a nickel film or a gold film, or a combination of at least two of them.
3. A method for preparing the LCP-based copper-clad laminate according to claim 1 or 2, characterized in that: The preparation method comprises: A first LCP film, a PTFE fiber cloth and a second LCP film stacked in sequence are heat pressed to obtain a high-frequency and high-speed LCP adhesive film; a first metal film and a second metal film are first deposited on both side surfaces of the obtained high-frequency and high-speed LCP adhesive film, and a first copper layer and a second copper layer are second deposited on the surfaces of the obtained first metal film and the second metal film to obtain an LCP-based copper-clad laminate.
4. The preparation method according to claim 3, characterized in that: The temperature of the hot pressing is 270-320° C., the pressure is 3-10 MPa, and the pressing time is 50-120 min.
5. The preparation method according to claim 3 or 4, characterized in that: The first deposition method includes physical vapor deposition.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The first deposition method includes chemical plating and / or electroplating.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The preparation method further comprises performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film respectively before the thermal pressing; Preferably, the preparation method further comprises performing a second plasma treatment on both side surfaces of the obtained high-frequency and high-speed LCP film before the first deposition.
8. The preparation method according to claim 7, characterized in that: The gases used in the first plasma treatment and the second plasma treatment independently include any one of H2, NH3, Ar, O2 or CF4 or a combination of at least two thereof; Preferably, the gases used in the first plasma treatment and the second plasma treatment are independently H2, CF4 and O2 in a volume ratio of (1-2.5):1:1; Preferably, the flow rates of the gases used in the first plasma treatment and the second plasma treatment are independently 30 to 80 mL / min; Preferably, the power used in the first plasma treatment and the second plasma treatment is independently 200 to 2000 W; Preferably, the absolute vacuum degree in the first plasma treatment and the second plasma treatment is independently ≤1×10 - 6 Pa; Preferably, the temperature in the first plasma treatment and the second plasma treatment is independently 80 to 300° C.; Preferably, the duration of the first plasma treatment and the second plasma treatment is independently 5 to 60 minutes.
9. The preparation method according to any one of claims 3 to 8, characterized in that: The preparation method comprises: (1) performing a first plasma treatment on the surfaces of the first LCP film, the PTFE fiber cloth and the second LCP film respectively, and performing heat pressing for 50 to 120 minutes at a temperature of 270 to 320° C. and a pressure of 3 to 10 MPa on the first LCP film, the PTFE fiber cloth and the second LCP film, which are sequentially stacked and arranged after the first plasma treatment, to obtain a high-frequency and high-speed LCP adhesive film; (2) performing a second plasma treatment on both sides of the high-frequency and high-speed LCP film obtained in step (1), and then independently treating both sides of the high-frequency and high-speed LCP film after the second plasma treatment with a power of 5 to 60 kW, a temperature of 200 to 400° C., and a temperature of ≤1×10 -3 Pa, performing physical vapor deposition of a first metal film and a second metal film, and then independently depositing a first copper layer and a second copper layer on the surfaces of the obtained first metal film and the second metal film by chemical plating and / or electroplating, to obtain an LCP-based copper-clad laminate; The gases used in the first plasma treatment and the second plasma treatment independently include H2, CF4 and O2 in a volume ratio of (1-2.5):1:1; the flow rate of the gases used in the first plasma treatment and the second plasma treatment is independently 30-80 mL / min, the power used is independently 200-2000 W, and the absolute vacuum degree is independently ≤1×10 -6 Pa, the temperature is independently 80 to 300° C., and the time is independently 5 to 60 min.
10. An application of the LCP-based copper-clad laminate according to claim 1 or 2, characterized in that: The LCP-based copper clad laminate is used as a raw material in the high-frequency and high-speed fields.
Citation Information
Patent Citations
Liquid crystal polymer glass fiber bonding sheet copper-clad plate and preparation method thereof
CN102922809A
High -frequency and high -speed base plate
CN208175088U
Copper-clad laminate, printed wiring board, multilayer printed wiring board, and methods for producing those
CN101277816A
High-frequency flexible copper-clad plate material with multi-layer structure and preparation method of high-frequency flexible copper-clad plate material
CN116330765A
Organic light emitting diode display and manufacturing method of the same
KR1020220060524A
Cited By
Composite adhesive film for high-frequency copper-clad plate as well as preparation method and application of composite adhesive film
CN120484716A